Fabrication and characterization of semiconductor nickel oxide (NiO) nanopeprintss manufactured using a facile thermal treatment - Hashem, Manal; Saion, Elias; Al-Hada, Naif Mohammed; Mohamed Kamari, Halimah; Shaari, Abdul Halim; Talib, Zainal Abidin; Paiman, Suriati; Ahmad Kamarudin, Mazliana (Elsevier, 2016)
In this paper, thermal treatment procedures were utilised to prepare crystalline nickel oxide semiconductor nanoparticles, derived from an aqueous solution. The solution consists of three compounds, primarily nickel nitrate, polyvinyl pyrrolidine and deionised H2O acting as metal precursor, capping agent and solvent, respectively. The solution was made prior to the drying, grinding and calcination at varying temperature settings up to 800°C. The scanning Electron Microscopy (SEM) images allowed a detailed study on the morphological of the monocrystalline grains which were obviously observed in the specimen, showing them to be almost identical in shape and size. The Infrared Fourier Transform (FTIR) and X-ray diffraction (XRD) results demonstrated a transformation of the amorphous structure at room temperature to the crystalline structure at higher temperatures during calcination process. The mean particle diameter and particle distribution were found to be directly proportional to temperature increased. The transmission electron microscopic (TEM) analysis revealed that the particle diameters vary between 15 and 35nm when temperature increased between 500 and 800°C. The composition of the specimens was delineated by energy dispersed X-ray spectroscopy (EDX), which identified nickel and oxygen atomic percentages in the final products. Optical characteristics were deducted from a UV–Vis reflectance spectrophotometer, which demonstrated the energy band gap decrement as the calcination temperatures increased. Magnetic properties were determined through electron spin resonance spectroscopy (ESR), which revealed the presence of unpaired electrons. The magnetic field resonance decreases along with an increase of the g-factor value as the calcination temperature increased from 500 to 800°C.